PENGARUH PEMBELAJARAN PROBLEM-BASED LEARNING BERBANTUAN LEMBAR KERJA PESERTA DIDIK DAN ALAT PERAGA TERHADAP PEMAHAMAN MATEMATIS DITINJAU DARI GENDER SISWA - Sintya Permata Ayu; Moh. Uzer Usman; Mery Noviyanti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article describes the effect of problem-based learning assisted by students’ worksheets and teaching aids on students’ mathematical understanding based on their gender. The research method used in this article was quasi-experimental, with a factorial research design. The research subjects involved the fourth-grade students at elementary school. Based on the data result, there was a difference in students’ mathematical understanding between the students who received the problem-based learning assisted by students’ worksheets and students who received the problem-based learning assisted by teaching aid. There was no difference between male and female students in students’ mathematical understanding. The mathematical understanding of male students who received problem-based learning assisted by students’ worksheets was lower than male students who received problem-based learning assisted by teaching aids. The mathematical understanding of female students who received problem-based learning assisted by students’ worksheets was higher than female students who received problem-based learning assisted by teaching aids. And the test result showed that there was an interaction effect between problem-based learning and gender on students’ mathematical understanding